Antimicrobial Efficacy of Nano-Hydroxyapatite-Coated Implants Against Peri-Implantitis-Associated Bacteria - Neeraj Sharma; Jyotsna Shukla; Shuchi Jain; Rituparna Vyas; Tarun Verma; Bhumika Navlani (Journal of Pharmacy and Bioallied Sciences)
Background: Peri-implantitis, an inflammatory condition caused by bacterial biofilms on dental implants, is a leading cause of implant failure. Nano-hydroxyapatite (nHA) coatings have been proposed to enhance the antimicrobial properties of implants and promote osseointegration. This study evaluates the effectiveness of nHA-coated implants in inhibiting peri-implantitis-associated bacterial growth. Materials and Methods: Titanium dental implants were coated with nHA using the sol-gel technique. Bacterial strains commonly associated with peri-implantitis, including Porphyromonas gingivalis, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans, were cultured. The antimicrobial efficacy of nHA-coated and uncoated implants was tested using biofilm formation assays, bacterial viability assays, and scanning electron microscopy (SEM) to evaluate biofilm adhesion. Statistical analysis was conducted using ANOVA with P < 0.05 considered significant. Results: nHA-coated implants showed a significant reduction in bacterial adhesion and biofilm formation compared to uncoated implants (P < 0.01). The reduction rates for P. gingivalis, F. nucleatum, and A. actinomycetemcomitans were 78%, 65%, and 72%, respectively. SEM analysis revealed a smoother surface with less biofilm accumulation on nHA-coated implants. Additionally, nHA-coated surfaces exhibited enhanced antimicrobial activity without compromising biocompatibility. Conclusion: Nano-hydroxyapatite coatings effectively reduce bacterial colonization and biofilm formation on implant surfaces, demonstrating their potential to mitigate peri-implantitis, and improve implant longevity. Future studies should focus on clinical trials to confirm these findings in vivo.